Tensile bond strength and SEM analysis of enamel etched with Er:YAG laser and phosphoric acid: a comparative study In vitro - Sasaki,Luis H. (2008)
Er:YAG laser has been studied as a potential tool for restorative dentistry due to its ability to selectively remove oral hard tissue with minimal or no thermal damage to the surrounding tissues. The purpose of this study was to evaluate in vitro the tensile bond strength (TBS) of an adhesive/composite resin system to human enamel surfaces treated with 37% phosphoric acid, Er:YAG laser (lambda=2.94 mum) with a total energy of 16 J (80 mJ/pulse, 2Hz, 200 pulses, 250 ms pulse width), and Er:YAG laser followed by phosphoric acid etching. Analysis of the treated surfaces was performed by scanning electron microscopy (SEM) to assess morphological differences among the groups. TBS means (in MPa) were as follows: Er:YAG laser + acid (11.7 MPa) > acid (8.2 MPa) > Er:YAG laser (6.1 MPa), with the group treated with laser+acid being significantly from the other groups (p=0.0006 and p= 0.00019, respectively). The groups treated with acid alone and laser alone were significantly different from each other (p=0.0003). The SEM analysis revealed morphological changes that corroborate the TBS results, suggesting that the differences in TBS means among the groups are related to the different etching patterns produced by each type of surface treatment. The findings of this study indicate that the association between Er:YAG laser and phosphoric acid can be used as a valuable resource to increase bond strength to laser-prepared enamel.